Intramural neurofibroma of the trachea treated by multiple stents. Issue 7 (1st July 2001) - Cranshaw, J H; Morgan, C; Knowles, G; Nicholson, A G; Goldstraw, P
Abstract : The case history is presented of a patient in whom an intramural tracheal neurofibroma developed, causing severe airway stenosis. The patient was treated with multiple stents over a period of 5 years because of progression of the disease and associated airflow limitation. Clinicians should be aware of this rare complication of neurofibromatosis.